2016
DOI: 10.1016/j.celrep.2015.12.099
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of the CD4 T Cell Alloresponse: The Short and the Long of It

Abstract: SummaryMHC alloantigen is recognized by two pathways: “directly,” intact on donor cells, or “indirectly,” as self-restricted allopeptide. The duration of each pathway, and its relative contribution to allograft vasculopathy, remain unclear. Using a murine model of chronic allograft rejection, we report that direct-pathway CD4 T cell alloresponses, as well as indirect-pathway responses against MHC class II alloantigen, are curtailed by rapid elimination of donor hematopoietic antigen-presenting cells. In contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 51 publications
3
52
0
1
Order By: Relevance
“…6,28 Such a use of third-party T-regs to block host humoral alloimmunity would be distinctly different from proposed strategies that differentiate/expand T-regs with self-restricted specificity for alloantigen from the individual's endogenous T cell population, 25,33 and may offer a particular advantage. 37 This approach may have wider uses beyond transplantation. [34][35][36] Thus, for maximum effectiveness, recipient-derived T-regs would need to recognize the relevant allopeptide epitope presented by host MHC class II.…”
Section: Discussionmentioning
confidence: 99%
“…6,28 Such a use of third-party T-regs to block host humoral alloimmunity would be distinctly different from proposed strategies that differentiate/expand T-regs with self-restricted specificity for alloantigen from the individual's endogenous T cell population, 25,33 and may offer a particular advantage. 37 This approach may have wider uses beyond transplantation. [34][35][36] Thus, for maximum effectiveness, recipient-derived T-regs would need to recognize the relevant allopeptide epitope presented by host MHC class II.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, CD25 16,17 , CD69 17,18 , CD71 16,17 , CD134 19 , CD137 19,20 , CD154 19 and LFA1α 21 have been used in transplantation to identify alloreactive T cells. The glycoproteins CD44 21–23 or CD45 isoforms 24 , markers of antigen experience, are also used to distinguish naive from effector and memory cells. Markers of cell-cycle entry such as Ki67 can also identify recently activated T cells 23 .…”
Section: Detecting Alloreactive T Cells Following Alloantigen Stimulamentioning
confidence: 99%
“…The glycoproteins CD44 21–23 or CD45 isoforms 24 , markers of antigen experience, are also used to distinguish naive from effector and memory cells. Markers of cell-cycle entry such as Ki67 can also identify recently activated T cells 23 . Additionally, labeling responder PBMCs with intracellular dyes such as carboxyfluorescein succinimidyl ester (CFSE), whose fluorescence intensity is halved with each cell division, has been used to identify proliferating donor-reactive T cells following culture in an MLR 25 .…”
Section: Detecting Alloreactive T Cells Following Alloantigen Stimulamentioning
confidence: 99%
See 1 more Smart Citation
“…While donor MHC-peptide complexes is directly recognized by recipients' T cell in the former, allo-MHC is processed and re-presented by recipient antigen-presenting cells (APCs) in the indirect pathway, which plays a dominant role in the long term based on the continuous shedding of alloantigen from the graft. By using an adoptive transfer model of transgenic T cells in a murine chronic cardiac transplant model, Ali et al elegantly showed that the direct-pathway CD4 T cells are short lived, mostly due to the quick elimination of donor-derived APCs, while the indirect-pathway CD4 T cell responses are persistent and heterogeneous in terms of duration and sites, depending on the targeted alloantigen (1): donor-MHC I-specific responses taking place in allograft parenchyma last long, whereas anti-MHC II responses decay earlier due to donor APCs eradication. These findings highlight the importance of restraining the indirect allorecognition, in particular against donor MHC class I molecules, to prevent chronic cellular-mediated rejection.…”
Section: Introductionmentioning
confidence: 99%